How do Purple Sandpipers Calidris maritima survive the winter north of the Arctic circle? - Summers, R.W.; Piersma, T.; Strann, K.B.; Wiersma, P. (1998)
Winter north of the Arctic circle in northern Norway is colder, windier and there is less solar radiation than in eastern Scotland, at a latitude 13 degrees further south. We predicted from equations derived from heated taxidermic mounts that the maintenance metabolism (Basal Metabolic Rate plus extra costs for thermoregulation) for Purple Sandpipers Calidris maritima wintering in these climatic conditions in Norway would be 1.3 times greater than for Purple Sandpipers of the same size in Scotland. Adaptations to the more extreme environment and greater energy requirements were investigated by measuring differences in the body size and composition of Purple Sandpipers from northern Norway and Scotland. As predicted, the Norwegian Purple Sandpipers had more fat stores, but these were still at relatively low levels (6.5% of fresh body mass) compared with other waders wintering in cold climates. The Norwegian birds were slightly larger so will probably have a relatively lower thermal conductance than Scottish birds. Also, there were large differences in the relative sizes of the intestine (1.5 times heavier in Norwegian birds) and liver (1.3 times heavier). This suggests Bat Purple Sandpipers wintering in Norway eat and process a greater amount of food than the birds in Scotland. Ln this way, the additional energy demands for thermoregulation in a colder environment are probably met.